439. Corowa-kun: Impact of a COVID-19 Vaccine Information Chatbot on Vaccine Hesitancy, Japan 2021. (4th December 2021) - Kobayashi, Takaaki; Nishina, Yuka; Tomoi, Hana; Harada, Ko; Matsumoto, Eiyu; Inaba, Kanako; Ishihara, Jun; Sasaki, Shugo; Horimukai, Kenta; Seguchi, Kyosuke; Tanaka, Kyuto; Takahashi, Hiromizu; et al.
Abstract: Background: Japan has one of the highest vaccine hesitancy rates in the world. According to a previous study, less than 30% of people strongly agreed that vaccines were safe, important, or effective. We created a COVID-19 vaccine information chatbot in a popular messenger app in Japan to answer COVID-19 vaccine frequently asked questions (FAQs) via text messages. We assessed the impact of chatbot text messages on COVID-19 vaccine hesitancy by conducting a cross-sectional survey among chatbot users. Methods: LINE is the most popular messenger app in Japan; about 86 million people in Japan (roughly two-thirds of the population) use this messenger app. Corowa-kun, a free chatbot, was created in LINE on February 6, 2021. Corowa-kun provides instant, automated answers to frequently asked COVID-19 vaccine questions. A cross-sectional survey assessing COVID-19 vaccine hesitancy was conducted via Corowa-kun during April 5 to 12, 2021. We included persons ages 16 years old and older who had not received a COVID-19 vaccine. The survey was written in Japanese and consisted of 21 questions. Corowa-kun's Consultation Room Corowa-kun is the mascot of an online chatbot. This chatbot in LINE is used to answer COVID-19 vaccine frequently asked questions (FAQs) via text messages. As of May 10th, 70 FAQs are available. Results: A total of 59, 676 persons used Corowa-kun during February to April 2021. The most commonly accessed message categories were: "I have (select comorbidity), can I get a COVID-19 vaccine?" (23%); followed by questions on adverse reactions (22%) and how the vaccine works (20%). 10, 192 users (17%) participated in the survey. Median age was 55 years (range 16 to 97), and most were female (74%). Intention to receive a COVID-19 vaccine increased from 59% to 80% after using Corowa-kun (p < 0.01). Overall, 20% remained hesitant: 16% (1, 675) were unsure, and 4% (364) did not intend to be vaccinated. Factors associated with vaccine hesitancy were: age 16 to 34 (odds ratio [OR] = 3.7, 95% confidential interval [CI]: 3.0–4.6, compared to age ≥65), female sex (OR = 2.4, Cl: 2.1–2.8), and history of another vaccine side-effect (OR = 2.5, Cl: 2.2–2.9). Being a physician (OR = 0.2, Cl: 0.1-0.4) and having received a flu vaccine the prior season (OR = 0.4, Cl: 0.3-0.4) were protective. COVID-19 vaccine acceptance increased and hesitancy decreased after using Corowa-kun, Japan, 2021 (n=10, 192) *There was a statistically significant difference in responses between before and after using Corowa-kun (p < 0.01, Chi-square test). Univariable logistic regression models of factors associated with COVID-19 vaccine hesitancy, Japan, 2021 (n=10, 192) Ref: reference NA: Logistic regression was not performed due to too small number (n≤3) Conclusion: Corowa-kun reduced vaccine hesitancy by providing COVID-19 vaccine information in a messenger app. Mobile messenger apps could be leveraged to increase COVID-19 vaccine acceptance. Disclosures: All Authors : No reported disclosures